Procurement of Health Services In The Emergency of Covid 19 - Mashudy Hermawan (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
The period of the Covid 19 pandemic made the central and regional governments work harder while still paying attention to the principles of good government governance. With the aim of saving the people from the Covid 19 virus, the government is implementing health programs, one of which is the provision of health and support facilities. It is necessary to apply the prudence of law in the process of procurement to avoid things that are against the applicable law. The purpose of this study is to examine the procurement during the Covid 19 pandemic. This research method uses a normative juridical method with a conceptual and statutory approach. Conclusion of research on the procurement of goods and services is a legal instrument to support public service activities, during the emergency of Covid 19, players in the procurement of medical devices / health support goods are encouraged to use legal aid if the price offered by the provider soars